Statistical mechanics : lecture notes - Likharev, K. K. (Konstantin Konstantinovich) (IOP (Series). Release 6., 2019)
Essential Advanced Physics is a series comprising four parts: Classical Mechanics, Classical Electrodynamics, Quantum Mechanics and Statistical Mechanics. Each part consists of two volumes, Lecture notes and Problems with solutions, further supplemented by an additional collection of test problems and solutions available to qualifying university instructors. This volume, Statistical Mechanics: Lecture notes, is intended to be the basis for a one-semester graduate-level course on thermodynamics and statistical mechanics. The structure of the course is mostly traditional, besides that due to the current interest in nanoscale systems and ultrasensitive physical measurements, large attention is given to classical and quantum fluctuations of various physical variables. A brief introduction to physics kinetics is also included.